O uso da marca como alternativa inovadora no pagamento de credores em processos de falência e recuperação de empresas. - Gadelha Junior, Grinaldo (2019)
Judicial bankruptcy and judicial recovery processes, in general, go through for years and the scarce means of making available material resources of the companies, make it impossible to comply with the entire settlement and/or judicial recovery plan. Within the creative industries, the "trademark" originated from the intellectual creation of market professionals, constitutes an intangible good, generally underestimated and not valued properly. Thus, the possibility of innovating in the vision and valuation of the "trademark”, can, in the scope of the companies in situation of bankruptcy or judicial recovery, ruled by Laws 7.661/45 and 11.101/05, respectively, give rise to an effective alternative of obtaining resources for the payment of creditors and compliance with the liquidation and/or judicial recovery plan.